KAJIAN FENOMENOGRAFI ASPEK-ASPEK MODEL MENTAL SUBYEK LINTAS LEVEL AKADEMIK DALAM PROBLEM SOLVING KONSEP DASAR MEKANIKA - Mansyur, Jusman (2010)
The aims of study are to elicit the subjects' mental model and its aspects that include the external representation system, strategies, cognitive elements and knowledge structure in physics problem solving. The naturalistic study was conducted using phenomenographic approach to analyze the data from the individual thinking-aloud and the semi-structured interview to 9 students and 7 physics teachers from the senior high schools, 6 first and 7 third semester students from the physics education program, and 4 graduate students. The subjects were determined by selection test, except the teachers. Study results show that utilization of the external representation especially the diagram in the initial stages determine the effectiveness of problem solving. The success key factor of the problem solving is simultaneous processes of reading or understanding the problem, constructing diagram, and identifying given and asked variables. Analysis of mental model shows that respondents' mental models depend on the context and setting of the phenomena displays. Findings of the study emphasize that a mental model differently played by individual in the problem solving interview setting. Several mental models and their activation behaviors are only found in the problem solving setting. Outcome space of traditional problem shows that the choice of respondents' strategies are influenced by their psychological factors, such as cognitive load in working memory, phenomena of mind set or functional fixedness. The strategies in solving Jeopardy problems of graphical are different from formula deconstruction type. The cognitive elements or resources are identified, i.e: p-prim, facet, coordination class (readout strategy and causal net), and mathematical form. Activation patterns of the resources are very dependent to the context and complexity of phenomena. The coherence of activated resource is different between respondents each other for the same concept domain. Coherence of knowledge structure in the context of kinematic/dynamic and work-energy concepts integration shows that for the same concept domain, the different individuals connected and organized their knowledge with different ways. Generally, the maturation of mental model and its aspects depends on academic level. The maturation is shown by domination and consistency of graduate students and teachers in the appropriate mental models, effective external representation system at initial stages of problem solving and strategy, completed deconstruction of Jeopardy problem, and high coherent cognitive element and knowledge structure. The transition of expertise from novice to expert dominantly occurs at the third semester students that enrolled the analytical Mechanics course. The main results of the dissertation are construction of theoretical framework that useful to strengthen the scientific aspects of the mental model and problem solving theory. It is recommended that the educators and researchers should concern the aspects of mental model and knowledge utilization in order to improve the educational results.